Menace: Methamphetamine in Rural Communities - Angela Smith Collins (Rural Nurse Organization; Binghamton University, 2008)
Over 35 million persons worldwide regularly use or abuse methamphetamines (WHO, 2008). This statistic then puts methamphetamine as the second most common abused drug after cannabis. Methamphetamine addiction differs from other illicit drugs such as cocaine or heroin. Drug addicts describe this drug as "one hit, one hook." This defining characteristic of crystal methamphetamine is that addiction appears to occur upon first use. Methamphetamine use causes multiple anatomical defects in the brain and damages the frontal decision-making center. The action of the drug on the dopamine and serotonin-containing neurons creates false circuits. Even upon discontinuation of the drug, antipsychotic treatments are often required (National Institute of Drug Abuse, 2006). The consequences of these illicit drugs can be the destruction of families, depression, anxiety, paranoia, aggression, cardiovascular events, sexual abuse, and child endangerment (Grant, Kelley, Agrawal, Meza, Meyer, & Romberger, 2007). DEA (2008) statistics report that 20 percent of the meth labs seized last year had children present on site. Children are even more vulnerable to the life time consequences of the toxins of methamphetamines on both pulmonary and neurological systems. Methamphetamines are at the epicenter of circles of addiction that cause health consequences throughout our global community.